Synchronization for a Fuzzy Cellular Neural Networks with Mixed Time Delays. Issue 1 (March 2020) - Halik, Azhar; Mahemuti, Rouzimaimaiti
Abstract: This paper investigates the general decay synchronization (GDS) for fuzzy cellular neural networks (FCNNs). Compared with previous research results, constant time delays and distributed time delays are taken into consideration. By using the Lyapunov function method and some inequality techniques, several sufficient conditions are derived on the GDS for FCNNs. Ultimately, a numerical example is also carried out to validate the practicability and feasibility of our proposed results.